2017
DOI: 10.1007/jhep08(2017)130
|View full text |Cite
|
Sign up to set email alerts
|

Higgsed Gauge-flation

Abstract: We study a variant of Gauge-flation where the gauge symmetry is spontaneously broken by a Higgs sector. We work in the Stueckelberg limit and demonstrate that the dynamics remain (catastrophically) unstable for cases where the gauge field masses satisfy γ < 2, where γ = g 2 ψ 2 /H 2 , g is the gauge coupling, ψ is the gauge field vacuum expectation value, and H is the Hubble rate. We compute the spectrum of density fluctuations and gravitational waves, and show that the model can produce observationally viable… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
60
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 52 publications
(62 citation statements)
references
References 49 publications
2
60
0
Order By: Relevance
“…We thus showed that the frozen solution with an exponential potential and an exponential metric function is always stable, and hence this critical point is a dynamical attractor for all parameter values (assuming p ρ , L ρ > 0). Linearized stability in the more general case with non-exponential functions requires the expression 15) to be negative. Using the adiabatic/entropic decomposition reviewed in Sec.…”
Section: Critical Points Analysismentioning
confidence: 99%
“…We thus showed that the frozen solution with an exponential potential and an exponential metric function is always stable, and hence this critical point is a dynamical attractor for all parameter values (assuming p ρ , L ρ > 0). Linearized stability in the more general case with non-exponential functions requires the expression 15) to be negative. Using the adiabatic/entropic decomposition reviewed in Sec.…”
Section: Critical Points Analysismentioning
confidence: 99%
“…The tensor tilt n (vac) T is thus always negative and has a typical magnitude O(10 −2 ) or smaller. On the contrary, the spectrum of gravitational waves that are sourced through axion-gauge dynamics or higherorder gauge interactions can have a blue tilt [29,53]. In the specific case of Type I potentials, n power T is given by Eq.…”
Section: Type I and Ii Potentialsmentioning
confidence: 99%
“…Further implications of such a coupling to SM gauge groups are the presence of primordial magnetic fields and even a possible contribution to baryogenesis, see e.g. [52][53][54] for recent works. However it is also possible to imagine more complicated scenarios.…”
Section: µ-Type Distortions In the Cmbmentioning
confidence: 99%